2013
DOI: 10.1007/s00280-013-2366-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cisplatin-resistant human tumor cells with metabolic inhibitors

Abstract: Altered hexokinase levels in cisplatin-resistant cancer cell lines leads to increased sensitivity to glycolytic inhibition under anaerobic conditions, whereas under normoxic conditions, blockage of either fatty acid oxidation or deprivation of glutamine leads to cell death. These findings may be clinically applicable when considering cisplatin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…Such inherent differences were also observed in the LDHA and lactate levels after treatment with miR34a HA-NPs between the cisplatin sensitive and cisplatin resistant A549 and A549 DDP cells. This is consistent with the previous findings which depict the role of LDHA levels for acquired platinum resistance in cancer 82, 83 .…”
Section: Discussionsupporting
confidence: 94%
“…Such inherent differences were also observed in the LDHA and lactate levels after treatment with miR34a HA-NPs between the cisplatin sensitive and cisplatin resistant A549 and A549 DDP cells. This is consistent with the previous findings which depict the role of LDHA levels for acquired platinum resistance in cancer 82, 83 .…”
Section: Discussionsupporting
confidence: 94%
“…Preclinical studies have shown enhanced anti-tumor activity in pancreatic models with a variety of drugs including gemcitabine [34]. Cisplatin has demonstrated enhanced cytotoxicity in combination with 2-DG in head and neck cancer cells and in lung cancer cell lines [35,36]. Cisplatin-resistant cancer cell lines with decreased hexokinase levels have been shown to be more sensitive to the combined activity of cisplatin with 2-DG or 2-fluorodeoxyglucose [31].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of HK-II with siRNA reduces its mRNA and protein levels, as well as its activity, resulting in cell cycle arrest at the G1 phase, attenuated glycolysis, and apoptosis in cancer cells [31, 7678]. Silencing of the HK-II gene sensitizes human colon cancer cells to 5-fluorouracil [79] and sensitizes parental lung cancer cells to cisplatin [80]. In addition, the combination of HK-II interference and 131 I therapy demonstrated a stronger anticancer effect in anaplastic thyroid carcinoma cells [81].…”
Section: Agents Targeted Inhibiting the Hk-ii-mediated Warburg Effectmentioning
confidence: 99%